SCULPTOR OF THE PLANT USEFUL FEATURES AND GASTROINTESTINAL TRACT DISEASES IN TREATMENT INSTEAD OF - Khayatova Shoira Telmonovna; Abdukadirova Nargiza Batirbekovna (Web of Journals Publishing, 2024)
Healing plants from long ago medical of treatments main weapon being came Modern also medicine in medicine 45 percent of drugs from plants separate is taken. In phytotherapy each one plant to himself special way the pain relaxing, refreshing, calming, heart activities improving, hypotension and hypertension, inflammation against, sputum mover and perspiration such as series to the effects have Especially gastrointestinal in the activity appetite open, eat digestion to do and drink in pushing efficient using is getting married
Keywords: antidysenteric, asteraceae, gastritis.